(untitled) (Journal of Information Technologies in Education (ITE), 2013)
This Article is dedicated to the development of the modern methodological foundation based on ICT to support the teaching process of theoretical mechanics in pedagogical universities in the "Mathematics" specialty. Proposed metodological system is based on methodological multimedia teaching complex, made of internet-capable software products. The Paper covers the methodological issues of using individual elements of the complex at various stages of the learning process.